Polyalthia kinabaluensis - Hoo, P.K.; Colin Ruzelion Maycock; Damit, A.; Nilus, R.; Sugau, J.; Tanggaraju, S.; Tsen, S.; Pereira J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Polyalthia kinabaluensis is restricted to the lower montane region of Mount Kinabalu, Sabah. Due to extensive agricultural activities, this species experienced decline outside of protected areas. The estimated area of occupancy (AOO) and extent of occurrence (EOO) declined from 8 km2 to 4 km2. The subpopulation in Tenpompok is stable, but outside this area population trend is unknown. Hence, it is assessed as Critically Endangered. Polyalthia kinabaluensis is endemic to Sabah, Malaysia. It is restricted to the lower montane region of Mount Kinabalu.